The Standard periodical directory. (New York Oxbridge Communications, 1967)
This directory may be used to identify specialized trade journals as possible sources of business information or advertising.
Keywords: American periodicals -- Directories; Canadian periodicals -- Directories; Periodicals -- Canada -- Bibliography; Periodicals -- United States -- Bibliography